1976
DOI: 10.1002/chin.197604237
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ALKYLOXY AND SILYLOXY DERIVATIVES OF PHOSPHORUS(V) AND ANTIMONY(V)

Abstract: Nach einleitenden Untersuchungen zur Thermolyse der Alkoxy‐Verbindungen (I) wird deren Reaktion und die von (II) mit Triphenylsilanol (III) zu (IV) bzw. (VII) beschrieben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…An organoantimony betaine product was postulated to be formed when pentaphenylbismuth was reacted with triphenylantimony in carbon tetrachloride solution. 96 The betaine was neither isolated nor detected, the reaction mixture being treated with hydrogen chloride.…”
Section: Oxidation Reactions With Pentavalent Organobismuthmentioning
confidence: 98%
See 3 more Smart Citations
“…An organoantimony betaine product was postulated to be formed when pentaphenylbismuth was reacted with triphenylantimony in carbon tetrachloride solution. 96 The betaine was neither isolated nor detected, the reaction mixture being treated with hydrogen chloride.…”
Section: Oxidation Reactions With Pentavalent Organobismuthmentioning
confidence: 98%
“…In moist pyridine, the products included phenol and diphenyl ether, diphenyl ether being formed by reaction of pentaphenylbismuth with phenol. 95 In the presence of tert-butyl alcohol, tert-butyl phenyl ether was obtained. Diels-Alder addition products were obtained with furan and with 2,3,4,5-tetraphenylcyclopentadienone.…”
Section: Oxidation Reactions With Pentavalent Organobismuthmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistic Considerations.-We have previously suggested that reaction of 2-naphthol(l) with pentavalent organobismuth reagents (Ph,BiX or Ph,Bi) under neutral conditions involves the formation of an intermediate (4)3 possessing a covalent bismuth-xygen bond, and that the breakdown of this intermediate to give l-phenyl-2-naphthol (2) or 2-naphthyl phenyl ether (3) is determined by the nature of the ancillary group X (X = electron-withdrawing group or phenyl) in the intermediate (4). Our reason for postulating the existence of the intermediate (4) was provided by the observation that in addition to the product (3), benzene was also formed when 2-naphthol (1) was treated with tetraphenylbismuth trifluoro- acetate under neutral condition^.^ We postulated that the breakdown of the intermediate (4) occurred to give either 2-naphthyl phenyl ether (3) when the group X was strongly electron-withdrawing, or l-phenyl-2-naphthol (2) when the group X was phenyl. In accord with this postulate, 2-naphthol (1) and tetraphenylbismuth trifluoroacetate afforded, under neutral conditions with elimination of benzene only, the Ophenylated product (3),3 whereas 2-naphthol (1) and pentaphenylbismuth afforded only the C-phenylated product (2).…”
mentioning
confidence: 99%